Information Systems 19th European, Mediterranean, and Middle Eastern Conference, EMCIS 2022, Virtual Event, December 21-22, 2022, Proceedings - Papadaki, Maria; Rupino da Cunha, Paulo; Themistocleous, Marinos; Christodoulou, Klitos (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes selected papers from the 19th European, Mediterranean, and Middle Eastern Conference, EMCIS 2022, which was held virtually during December 7-8, 2022. EMCIS covers technical, organizational, business, and social issues in the application of information technology and is dedicated to the definition and establishment of Information Systems (IS) as a discipline of high impact for IS professionals and practitioners. It focuses on approaches that facilitate the identification of innovative research of significant relevance to the IS discipline following sound research methodologies that lead to results of measurable impact. The 47 papers presented in this volume were carefully reviewed and selected from a total of 136 submissions. They were organized in topical sections named: Artificial intelligence; big data and analytics; blockchain technology and applications; cloud computing; digital governance; digital services and social media; emerging computing technologies and trends for business process management; enterprise systems; information system security and information privacy protection; innovative research projects; IT governance and alignment; management and organizational issues in information systems; and metaverse.
Artificial Intelligence -- How Blockchain and Artificial Intelligence influence Digital Sovereignty -- The Concept of a New Neural Map for Clustering, Data Visualization and Prediction with Probability Distribution Approximation -- Significance of Eco-Cement constituents to its mechanical properties, by Machine Learning Algorithms -- Next Generation Process Material Tracking and Analytics for the Process Industries Using Machine Learning Algorithms -- Identification of multiple sclerosis signals' dependence on patients' medical conditions through stochastic perturbation of features in five machine learning models -- Big Data and Analytics -- Applying Predictive Analytics Algorithms to Support Sales Volume Forecasting -- AIOps in Higher Education Institutions -- Digital Content Profiling Based on User Engagement Features -- A Sensor-based Unit for Diagnostics and Optimization of Solar Panel Installations -- Big Data in the innovation process - a bibliometric analysis. -Blockchain Technologyand Applications -- EduCert - Blockchain-based management information system for issuing and validation of academic certificates -- A Distributed Multi-Key Generation protocol with a new complaint management strategy -- The Importance of Blockchain for Ecomobility in Smart Cities: A Systematic Literature Review -- Blockchain Governance - A Systematic Literature Review -- Cloud Computing -- Cybersecurity and Information Quality in Cloud Computing: A research Framework -- Browser extension for detection of fake news and disinformation -- Digital Governance -- A comprehensive framework for measuring governments' digital initiatives including open data -- Digital Solutions to What? - WPR as a model for public servants seeking a better grip on their local digitalization policy -- Concept for an open data ecosystem to build a powerful data environment -- Extending the "Smart City" Concept to Small -to-Medium Sized Estonian Municipalities: Initiatives and Challenges Faced -- Tools for calculating the ICTfootprint of organisations: adaptation of a European study -- Designing an API for the provision of Public Service information based on CPSV-AP -- An AI-enhanced solution for large-scale deliberation mapping and explainable reasoning -- Digital Services and Social Media -- Fairness Issues in Algorithmic Digital Marketing: Marketers' Perceptions -- The Importance of Platforms to achieve Digital Maturity -- Can Process Mining Detect Video Game Addiction Through Player's Character Class Behavior -- Evaluating Government University Digital Distance Learning Policies in the Covid-19 Period -- The determinants of technology acceptance for social media messaging applications - fixed-effect questionnaire design -- Conceptual Model of User Experience for Personalization -- Emerging Computing Technologies and Trends for Business Process Management -- Mining Contextual Process Models Using Sensors Data: a Case of Daily Activities in Smart Home -- Business Process Automation in SMEs -- An Integrated Approach Using Robotic Process Automation and Artificial Intelligence as Disruptive Technology for Digital Transformation -- Modern warehouse and delivery object monitoring - safety, precision, and reliability in the context of the use the UWB technology -- Enterprise Systems -- The effects of artificial intelligence in the process of recruiting candidates -- Information System Security and Information Privacy Protection -- Security Risk Assessment of Blockchain-based Patient Health Record Systems -- Domain and Semantic Modeling in the context of Interactive Systems Development: User and System cases -- A Review of Internet of Things (IoT) Forensics Frameworks and Models -- Innovative Research Projects -- Local Energy Markets: A Market Transformation Survey towards Segments of Interest -- IT Governance and Alignment -- Towards a Taxonomy of Strategic Drivers of IT Costs -- The Digital Operational Resilience Act for Financial Services: A Comparative Gap Analysis and Literature Review -- Management and Organizational Issues in Information Systems -- Towards Analytical Business Services as a New Business Model for Shared Service Centers -- Remote Working from a Management Perspective -- Image analysis and processing for generating camouflages from satellite photographs -- Bibliometric analysis of publications on evacuation of Hazards using GIS as a decision support tool from the Scopus database -- A Bibliometric Analysis of Digital Transformation for a Resilient Organization -- Metaverse -- Virtual Immersive Workplaces: The New Norm? - A Qualitative Study on the Impact of VR in the Workplace -- An Educational Metaverse Experiment: The first on-chain and in-Metaverse academic course.
Keywords: Application software; Business information services; Computer security; Electronic data processing -- Management; Big data; Social media; Computer and Information Systems Applications; IT in Business; Principles and Models of Security; IT Operations; Big Data; Social Media